2022
DOI: 10.1038/s41419-022-05162-4
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 promotes prostatic hyperplasia by regulating PTEN expression in an m6A-YTHDF2-dependent manner

Abstract: Uncontrolled epithelial cell proliferation in the prostate transition zone and the hyper-accumulation of mesenchymal-like cells derived from the epithelial-mesenchymal transition (EMT) of prostatic epithelium are two key processes in benign prostatic hyperplasia (BPH). m6A RNA modification affects multiple cellular processes, including cell proliferation, apoptosis, and differentiation. In this study, the aberrant up-regulation of methylase METTL3 in BPH samples suggests its potential role in BPH development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A comprehensive understanding of the intricate processes underlying proliferative nodules holds immense clinical significance in terms of identifying novel therapeutic targets for BPH. Previous studies have indicated that, apart from LE cells which are targeted by 5-ARIs, other cell types within the prostate have been implicated in this pathogenesis [ 10 , 12 , 41 43 ], highlighting their potential as therapeutic targets for BPH. However, due to technological limitations, their contributions have yet to be validated through in vivo investigations conducted on patients with BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive understanding of the intricate processes underlying proliferative nodules holds immense clinical significance in terms of identifying novel therapeutic targets for BPH. Previous studies have indicated that, apart from LE cells which are targeted by 5-ARIs, other cell types within the prostate have been implicated in this pathogenesis [ 10 , 12 , 41 43 ], highlighting their potential as therapeutic targets for BPH. However, due to technological limitations, their contributions have yet to be validated through in vivo investigations conducted on patients with BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Although several cellular processes have been reported to be involved in BPH initiation and development, Its specific mechanism is largely unknown. The contribution of androgen response [ 6 , 7 ], hypoxia [ 8 , 9 ], epithelial-mesenchymal transition (EMT) [ 10 12 ], etc. in prostatic epithelium to the development of BPH has been acknowledged, highlighting the crucial role of epithelial cells in proliferative nodular formation.…”
Section: Introductionmentioning
confidence: 99%
“…METTL3, an m6A methyltransferase, has oncogenic function in several human cancer 32 . By reducing METTL3 expression, cancer cells can be less capable of migrating, invading, and undergoing epithelial-mesenchymal transitions 33 , 34 . YTHDF1 is highly expressed in colon cancer and knocking it down significantly inhibits the tumorigenicity of CRC cells in vitro 35 .…”
Section: Discussionmentioning
confidence: 99%
“…METTL3/14 complex mediates the m6A methylation of NAP1L2 mRNA, and LncRNA NAP1L6 recruits HNRNPC to the m6A sites of NAP1L2, promoting NAP1L2 mRNA stabilization, inducing cell migration, invasion, and enhancing EMT function [ 184 ]. METTL3 inhibits PTEN expression through the m6A-YTHDF2 modality and promotes prostate hyperplasia [ 185 ].…”
Section: Mettls In Tumor Proliferation Invasion and Metastasismentioning
confidence: 99%